2006
DOI: 10.1210/er.2006-0005
|View full text |Cite
|
Sign up to set email alerts
|

Germ Cell Tumors in the Intersex Gonad: Old Paths, New Directions, Moving Frontiers

Abstract: The risk for the development of germ cell tumors is an important factor to deal with in the management of patients with disorders of sex development (DSD). However, this risk is often hard to predict. Recently, major progress has been made in identifying gene-products related to germ cell tumor development (testis-specific protein-Y encoded and octamer binding transcription factor 3/4) and in recognizing early changes of germ cells (maturation delay, preneoplastic lesions, and in situ neoplasia). The newly rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
359
2
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 446 publications
(377 citation statements)
references
References 111 publications
5
359
2
11
Order By: Relevance
“…This lack-of-androgen theory would correlate with a significantly higher risk for tumor development in patients with partial androgen insensitivity syndrome (15% versus 0.8% in complete androgen insensitivity syndrome according to Cools et al). 4 Because we did not observe any significant differences in the persistence of POU5F1-positive germ cells and KITLG expression in relation to the expected level of AR activity among patients with complete androgen insensitivity syndrome, the residual activity of AR in complete androgen insensitivity is likely not powerful enough to achieve a similar effect on survival of abnormal germ cells and their progression into neoplasia as in partial androgen insensitivity. The result may be partly influenced by the relatively small sample size.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…This lack-of-androgen theory would correlate with a significantly higher risk for tumor development in patients with partial androgen insensitivity syndrome (15% versus 0.8% in complete androgen insensitivity syndrome according to Cools et al). 4 Because we did not observe any significant differences in the persistence of POU5F1-positive germ cells and KITLG expression in relation to the expected level of AR activity among patients with complete androgen insensitivity syndrome, the residual activity of AR in complete androgen insensitivity is likely not powerful enough to achieve a similar effect on survival of abnormal germ cells and their progression into neoplasia as in partial androgen insensitivity. The result may be partly influenced by the relatively small sample size.…”
Section: Discussionmentioning
confidence: 64%
“…5 The risk was estimated to be 0.8% in another meta-analysis, but this estimation was mainly based on a group of patients in which gonadectomy was carried out during childhood. 4 In fact, the risk is very difficult to predict because the approaches to manage patients with complete androgen insensitivity have continually changed over time. Whereas older reports included many adult patients and mainly reported the presence of invasive germ cell tumors, 6,28,29 more recent studies on pediatric patients refer to pre-invasive lesions, ie, intratubular germ cell neoplasia, of the testis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have shown carcinomatous changes in the testes of the children of CAIS in the age group of 13-14 years and it is believed that testicular biopsy is warranted as soon as the syndrome is diagnosed. Recent studies reveal a tumor incidence (dysgerminoma, gonadoblastoma) of 0.8 % in CAIS and 5.5 % in AIS overall, and the risk increases markedly after puberty and reaches 33 % at the age of 50 [1,2]. Thus, gonadectomy is advised after puberty.…”
Section: Discussionmentioning
confidence: 99%